Targeting Sphingolipids for Cancer Therapy - Companioni, Osmel; Mir, Cristina; Garcia-Mayea, Yoelsis; LLeonart, Matilde E. (Frontiers in Oncology, 2021)
Sphingolipids are an extensive classification of lipids that play different functions in the cell, ranging from proliferation to cell death. Sphingolipids are upregulated in a multitude of cancers and are responsible for tumor proliferation, progression, and metastasis. Several inhibitors or activators of sphingolipid signaling, such as fenretidine, safingol, ABC294640, ceramide nanoliposomes, SKI-II, α-galactosylceramide, fingolimod, and sonepcizumab, have been described. The objective of this review was to analyze the results from preclinical and clinical trials of these drugs for the treatment of cancer. Sphingolipid-targeting drugs have been tested alone or in combination with chemotherapy, exhibiting antitumor activity alone as well as in synergism with chemotherapy in vitro and in vivo. As a consequence of treatments, the most frequent mechanism of cell death is apoptosis followed by autophagy. Although all these drugs have indicated good results in preclinical studies of multiple cancers, the landscape for clinical trials has not been similar. The most effective drugs are α-galactosylceramide (α-GalCer), fenretinide, and sonepcizumab. In contrast, minor adverse responses restricted to a few subjects and hepatic toxicity have been observed in clinical trials for ABC294640 and safingol, respectively. The effectiveness or lack of a major therapeutic effect of sphingolipid modulation as a cancer therapy for some drugs as well as other aspects related to their mechanism of action are discussed in this review.